COMPERA 2.0 risk stratification in medically managed chronic thromboembolic pulmonary hypertension. Issue 3 (15th September 2022) - Stubbs, Harrison; Lua, Stephanie; Brewis, Melanie; Johnson, Martin; Church, Colin
The COMPERA 2.0 model has been validated as a novel risk stratification system in pulmonary arterial hypertension (PAH), yet awaits validation in other causes of pulmonary hypertension [1, 2]. This study aimed to validate this model in patients with chronic thromboembolic pulmonary hypertension (CTEPH) who were either inoperable or had residual CTEPH following intervention. The newly proposed COMPERA 2.0 risk stratification model provides improved clinical refinement and is applicable in medically managed chronic thromboembolic pulmonary hypertension (CTEPH). https://bit.ly/3OPHyXU